2020
DOI: 10.1111/irv.12800
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of rapid influenza PCR in the adult emergency department on patient management, ED length of stay, and nosocomial infection rate

Abstract: Background Seasonal influenza causes significant morbidity and mortality and incurs large economic costs. Influenza like illness is a common presenting concern to Emergency Departments (ED), and optimizing the diagnosis of influenza in the ED has the potential to positively affect patient management and outcomes. Therapeutic guidelines have been established to identify which patients most likely will benefit from anti‐viral therapy. Objectives We assessed the impact of rapid influenza PCR testing of ED patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…However, the significant usefulness of early antiviral therapy for inpatients with influenza and PCR-based POCT for reducing nosocomial transmission of influenza has not been defined. 9,10,23,24 In this study, we found comparable clinical manifestations and outcomes between children with CA influenza and children with HA influenza. Previous reports have shown inconsistent results regarding increased clinical severity in patients with HA influenza compared to those with CA influenza.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, the significant usefulness of early antiviral therapy for inpatients with influenza and PCR-based POCT for reducing nosocomial transmission of influenza has not been defined. 9,10,23,24 In this study, we found comparable clinical manifestations and outcomes between children with CA influenza and children with HA influenza. Previous reports have shown inconsistent results regarding increased clinical severity in patients with HA influenza compared to those with CA influenza.…”
Section: Discussionsupporting
confidence: 63%
“…However, the significant usefulness of early antiviral therapy for inpatients with influenza and PCR-based POCT for reducing nosocomial transmission of influenza has not been defined. 9,10,23,24…”
Section: Discussionmentioning
confidence: 99%
“…31 Early rapid detection of influenza virus infection with implementation of early treatment and infection control measures has been shown to reduce hospital length of stay, to lower hospital occupancy, and to decrease the spread of HA influenza. 2,33,34 This study had several limitations. Influenza testing within FluSurv-NET is clinician-driven or based on different facility-based testing policies, which likely resulted in an underestimation of HA influenza cases, particularly among those who present with nonrespiratory symptoms or asymptomatically.…”
Section: Discussionmentioning
confidence: 97%
“…Altogether, these studies emphasize that rapid detection of respiratory viral infections directly in emergency departments could improve patient management and bed occupancy. Reducing the time of infected individuals in emergency wards could also limit the risks of nosocomial transmission ( 15 , 17 , 18 ). A recent study using another molecular POCT showed that its implementation in the ED was associated with a significant reduction in the rate of hospital-acquired COVID-19 cases ( 19 ).…”
Section: Discussionmentioning
confidence: 99%